DETERMINAN KINERJA INDUSTRI TPT INDONESIA - Nada, Haya Marshella Lifnatin; Hermawan, Iwan; Rambe, Khoiru Rizqy; Nugraheni, Reninta Dewi; Zuhdi, Fadhlan; Isnasari, Yovita; Asshagab, Sri Milawati (Jurnal Ekonomi Pembangunan, 2023)
The textile and textile product (TPT) industry is a leading industry for national economic growth. The existence of its performance relies on various factors that turn out to be vulnerable to fluctuations, including the fulfillment of raw materials in the form of cotton fiber from import dominance. Therefore, disruption of the performance of the textile industry will also stimulate disruption to Indonesia's economic growth. This study aims to analyze the determinants of the development of textile industry performance. For this reason, a quantitative approach is used with econometric models prepared based on the Cobb-Douglas theory of production functions. The model construction uses secondary time series data for the period 1992-2021 sourced from the World Bank, Bank Indonesia, the International Monetary Fund (IMF), and the Central Statistics Agency (BPS). The findings show that the terminology of the development of the performance of the Indonesian textile industry includes capital, labor absorption, world cotton fiber prices, inflation, textile exports, the Covid-19 pandemic, and the global food crisis in 2007/2008. Therefore, several policy recommendations were submitted to encourage more massive TPT machine restructuring programs, improve the skills of TPT human resources (HR), provide incentives for Local Ease of Export Destinations (KLTE), and re-intensify the #banggabuatanindonesia campaign.